Evaluating the Level of Job Involvement among Secondary School Teachers: Evidence from Murshidabad, West Bengal - Walid Masud; Dr. Yashpal Singh (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research investigates the level of job involvement among secondary school teachers, with a particular focus on their psychological identification with and emotional investment in their professional responsibilities. The concept of job involvement is crucial in understanding how teachers perceive their role in student development and institutional performance. For the present study, data were collected from a sample of 400 secondary school teachers using the Job Involvement Scale (JIS) developed by Dr. Zaki Akhtar and Dr. Udham Singh (2014). This scale comprises 20 items assessing teachers’ involvement based on their attitudinal and behavioral commitment toward their work. A one-sample t-test was employed to compare the obtained mean score with the standardized test value. The findings revealed that teachers demonstrated a statistically significant high level of job involvement (t = 25.96, p < 0.001), suggesting that they are deeply engaged with their professional duties and derive substantial meaning from their roles as educators. The low standard deviation indicates consistency across responses. These results imply that enhancing job involvement can be a strategic tool for improving educational outcomes. The study holds policy implications for educational administrators, indicating the need for supportive organizational environments that further enhance teacher engagement and satisfaction. Future research is recommended to explore the causal factors influencing job involvement across various school types and demographic profiles.
Keywords: Job involvement; secondary teachers; psychological engagement; JIS; educational psychology; West Bengal